Underground energy storage system supported resilience enhancement for power system in high penetration of renewable energy - Qin, Boyu; Shi, Wen; Fang, Ruoquan; Wu, Dongyang; Zhu, Yu; Wang, Hongzhen (Frontiers in Energy Research, 2023)
High penetration of renewable energy is becoming an important development trend in new generation power system. However, frequent extreme weather events and fragile renewable energy sources pose a huge challenge to the power system resilience. As an important support technology of renewables, energy storage system is of great significance in improving the resilience of the power system. In this paper, a resilience enhancement method for power systems with high penetration of renewable energy based on underground energy storage systems (UESS) is proposed. Firstly, a resilience assessment model is established and the influence of extreme weather is quantified as the failure rate of power system components. Secondly, a bi-level optimization model for UESS operation and planning under extreme weather is built, and the life cycle of UESS is considered. Finally, taking the modified IEEE RTS-79 as an example, the optimal scheme for UESS configuration and operation is given, the investment and effectiveness of UESS is also analyzed. The results show that UESS can significantly enhance the power system resilience under extreme weather events.